ADMINISTRATION OF THE STUDENT SUPPORT SYSTEM THAT AFFECTS ADMINISTRATION STUDENT AFFAIRS OF PRIVATE SCHOOLS UNDER OFFICE OF THE PRIVATE EDUCATION COMMISSION IN RATCHABURI PROVINCE - Kidnaitangdee, Suphapit; Jirarotephinyo, Nitwadee (Journal of MCU Nakhondhat, 2024)
The objective of this article research were: 1) To study the administrative level of the student support system under Office of the Private Education Commission, Ratchaburi Province. 2) To study the level of student affairs administration of private schools under Office of the Private Education Commission, Ratchaburi Province, and 3) To study the administration of the student support system that affects administration student affairs of private schools under Office of the Private Education Commission, Ratchaburi Province. This research is a survey research. The population includes administrators, guidance teachers, and counselors. in private schools under Office of the Private Education Commission, Ratchaburi Province. There were 23 schools, totaling 1,332 people. The sample group in the study included administrators, guidance teachers, counselors, private schools under Office of the Private Education Commission, Ratchaburi Province. There were 308 people using Taro Yamane's sample size calculation at a confidence level of 0.95. The research instrument was a questionnaire. Statistics used in data analysis include frequency, percentage, mean, standard deviation. and stepwise multiple regression analysis. The results of the research found that 1) The overall level of practice regarding the administration of the student care and support system of private schools was at a moderate level. ( = 3.24, S.D. = .585) 2) The overall level of practice regarding the principles of administration student affairs was at a moderate level. ( = 3.34, S.D. = .588) 3) Administration of the student support system that affects administration student affairs of private schools under Office of the Private Education Commission, Ratchaburi Province. There is a positive relationship with statistical significance at the .01 level by selecting Model 3 as the administrative model for the student support system that affects administration student affairs of private schools under Office of the Private Education Commission, Ratchaburi Province. There were 3 independent variables, that were able to contribute to the prediction of 50.5% with statistical significance at the .05 level.